2019
DOI: 10.1073/pnas.1910391116
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the oncoprotein transcription factor MYC with its chromatin cofactor WDR5 is essential for tumor maintenance

Abstract: The oncoprotein transcription factor MYC is overexpressed in the majority of cancers. Key to its oncogenic activity is the ability of MYC to regulate gene expression patterns that drive and maintain the malignant state. MYC is also considered a validated anticancer target, but efforts to pharmacologically inhibit MYC have failed. The dependence of MYC on cofactors creates opportunities for therapeutic intervention, but for any cofactor this requires structural understanding of how the cofactor interacts with M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
156
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(169 citation statements)
references
References 44 publications
13
156
0
Order By: Relevance
“…Altogether, Myc HEA lacks E-box recognition but retains the propensity to distribute along active chromatin when overexpressed, consistent with the notion that chromatin features (i.e. accessibility, composition, protein-protein interactions, etc…) rather than DNA sequence are the primary determinants of Myc binding (Guccione et al, 2006, Kim et al, 2008, Richart et al, 2016, Soufi et al, 2012, Thomas et al, 2019, Thomas et al, 2015. However, binding must also rely upon close contacts with the DNA backbone, as demonstrated by the loss of interaction seen with the Myc RA mutant.…”
Section: Differential Impairment In Genome Recognition By Myc Hea Andsupporting
confidence: 69%
See 1 more Smart Citation
“…Altogether, Myc HEA lacks E-box recognition but retains the propensity to distribute along active chromatin when overexpressed, consistent with the notion that chromatin features (i.e. accessibility, composition, protein-protein interactions, etc…) rather than DNA sequence are the primary determinants of Myc binding (Guccione et al, 2006, Kim et al, 2008, Richart et al, 2016, Soufi et al, 2012, Thomas et al, 2019, Thomas et al, 2015. However, binding must also rely upon close contacts with the DNA backbone, as demonstrated by the loss of interaction seen with the Myc RA mutant.…”
Section: Differential Impairment In Genome Recognition By Myc Hea Andsupporting
confidence: 69%
“…Myc dimerizes with Max (Blackwood & Eisenman, 1991) to bind DNA with a preference for the E-box consensus sequence CACGTG (Blackwell et al, 1993, Solomon et al, 1993, through which it activates transcription (Amati et al, 1992, Kretzner et al, 1992. Within cells, however, Myc promiscuously associates with active chromatin (Guccione et al, 2006, Kim et al, 2008, Soufi et al, 2012, owing most likely to a combination of general accessibility , protein-protein interactions (Richart et al, 2016, Thomas et al, 2019, Thomas et al, 2015 and non-specific DNA binding (Brownlie et al, 1997, Ferre-D'Amare et al, 1993, Nair & Burley, 2003, Sauvé et al, 2007:…”
Section: Introductionmentioning
confidence: 99%
“…we reasoned, then MYC should be evicted with it at co-bound genes. Indeed, we showed that WIN site inhibition is as effective at displacing MYC from chromatin at protein synthesis genes as genetic disruption of the MYC-WDR5 interaction 10 a manipulation that, as mentioned above, causes rapid and complete tumor loss. The effect of WIN site inhibitors on recruitment of MYC to chromatin is a notable advance with real practical consequences: The WIN site of WDR5 is much more druggable than the MYC site, and there are several groups that have distinct WIN site inhibitors thatin light of our recent workcould be repurposed for targeting MYC.…”
mentioning
confidence: 68%
“…Our recent studies have begun to overcome these obstacles. 8,9,10 In our most recent paper, 10 we studied the MYC-WDR5 connection in the context of Burkitt lymphoma, which is driven by a chromosomal translocation that places MYC expression under control of a potent immunoglobulin heavy chain enhancer. We learned that MYC and WDR5 co-bind to a fairly small group of genes that are manifestly connected to protein synthesis, including those encoding more than half of the proteins in the ribosome.…”
mentioning
confidence: 99%
See 1 more Smart Citation